Exchange Rate and Foreign Interest Rate Linkages for Sub-Saharan Africa Floaters - Thomas, Alun (IMF Working Papers; Working Paper ;, 2012)
The paper considers the determinants of exchange rate movements among sub-Saharan countries that have flexible exchange rate regimes. The determinants are based on the law of one price and interest parity conditions. Results indicate that the exchange rates have responded significantly to changes in the US Treasury bill rate and to the EMBI spread in recent years. The effects are more important for countries with open capital accounts. On the other hand the paper does not provide any support for the interest rate parity theory because domestic interest rates have no bearing on exchange rate movements.